2021
DOI: 10.3390/agriculture11121219
|View full text |Cite
|
Sign up to set email alerts
|

Germplasm Screening of Green Manure Rapeseed through the Effects of Short-Term Decomposition on Soil Nutrients and Microorganisms

Abstract: The rapidly emerging fertilizer rapeseed used as green manure has wide applications for use. However, there have been few studies on its decomposition and effects on soil nutrients and microorganisms after its decay. In this study, 12 rapeseed lines to be screened were decomposed through a randomized block field design with two green-manure-specific varieties as the controls. The contents of nitrogen, phosphorus, and potassium from the plants, soil nutrients, and microbial changes after degradation were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…As a positive control, ampicillin showed excellent activity of 19.65 mM ( E. coli ), 15.12 mM ( B. subtilis ), and 14.32 mM ( S. aureus ) at a dose of 50 μg/dis. Jo et al ( 59 ) found that stretch-responsive microcapsules could regulate the release of antibacterial compounds, results consistent with these findings.…”
Section: Resultssupporting
confidence: 63%
“…As a positive control, ampicillin showed excellent activity of 19.65 mM ( E. coli ), 15.12 mM ( B. subtilis ), and 14.32 mM ( S. aureus ) at a dose of 50 μg/dis. Jo et al ( 59 ) found that stretch-responsive microcapsules could regulate the release of antibacterial compounds, results consistent with these findings.…”
Section: Resultssupporting
confidence: 63%
“…The nitrogen (N), phosphorus (P), and potassium (K) contents of plants and soils were determined using previously defined conventional methods [30][31][32][33][34][35], and the data were analyzed as previously described [30].…”
Section: Test Methods and Data Analysismentioning
confidence: 99%
“…Soil microorganisms are important indicators of soil health, as they play an essential role in decomposing organic matter, cycling nutrients, and fertilizing soil [29]. Our previous studies have shown that the decomposition of rapeseed green manure does not change the main composition of soil microorganisms, but only affects their content [30]. However, this past research only analyzed the degradation of a single rapeseed variety under a single condition, which is insufficient for most applications and quite limited in scope.…”
Section: Introductionmentioning
confidence: 99%